Business track diplomacy: 4ocean effort in mitigation of plastic waste in Bali waters area - Anisha Primadita Rudyana; Najamuddin Khairur Rijal (Jurnal Inovasi Ilmu Sosial dan Politik (JISoP), 2022)
Environmental issues have become one of the global problems with a high degree of urgency. The province of Bali is one of the absolute highlights with evidence of a poor water quality index. In studying international relations, global problems can be solved through diplomatic instruments by interested countries. Uniquely, footage of phenomena in the field shows that there are non-governmental actors, namely business people, trying to solve environmental problems to lead to world peace. This study aims to examine 4Ocean's efforts to mitigate plastic waste in the waters of Bali. The author uses business track diplomacy to analyze the actions of 4Ocean. As a result, several measures have realized 4Ocean's efforts to carry out business line diplomacy in mitigating plastic pollution in Bali's waters. First, 4Ocean has sought to implement a sound business model by turning profits into reforestation operations. Second, 4Ocean has carried out plastic pollution operations in Bali as a whole, including river, coastal, and ocean operations. Third, 4Ocean has attempted to validate environmentally friendly products with B Corp, GOTS, and Green Circle Certified certifications.